Fostering CSR sponsorship in China: a conceptual framework for cultivating sustainable behavior among Ant Forest app users via internet platforms - Man, L.I.; Abdullah, Zulhamri; Syed Alsagoff, Syed Agil; Ibrahim, Rahinah (IBIMA Publishing, 2024)
Ant Forest has emerged as a prominent pro-environment advocate, amassing a user base of 650 million individuals. However, the sustained engagement of its users is crucial for its enduring success. To ensure the continued viability of Ant Forest, it is imperative to foster and maintain users' pro-environmental behaviors over an extended period. Central to Ant Forest's appeal are its gamification features and interactive elements linked to CSR sponsorship. This study aims to investigate the potential of these distinctive characteristics within an Internet platform to enhance users' awareness of sustainability issues and prolong their engagement. As part of a comprehensive inquiry into the role of Chinese Internet Platform Companies such as Ant Forest in shaping users' attitudes and behaviors towards sustainability, this research endeavors to ascertain whether these platforms fulfill their responsibility in offsetting carbon emissions. The present findings are from a thorough desktop survey focusing on key themes related to the Ant Forest app, including the maintenance of users' sustainable behavior and the enhancement of CSR sponsorship. Utilizing the EAGLE System, an online research platform, we meticulously documented the synthesis of literature reviews and adapted the findings for presentation. Our analysis identified CSR-linked sponsorship, the sustainability of Chinese Internet Platform Companies, users' behavior, and users' attitudes as potential independent variables. Furthermore, we identified the gamification mechanism and interactivity as moderator variables influencing users' engagement with their responsibilities in carbon emissions offsetting. Notably, Chinese Internet platform companies have the potential to positively influence users' attitudes and behaviors towards sustainability by integrating gamification, interactivity, and CSR-linked sponsorship into their platforms. Harnessing these features effectively may empower Internet platforms to instill sustainable habits among users, thereby laying the groundwork for a conceptual framework termed the Users' Sustainable Awareness Model. © 2024. Man LI, Zulhamri ABDULLAH, syed agil SYED ALSAGOFF and Rahinah IBRAHIM. Distributed under Creative Commons Attribution 4.0 International CC-BY 4.0.